STRATEGI PEMASARAN KERIPIK TEMPE DI DESA SRI MULYA KECAMATAN SINAR PENINJAUAN KABUPATEN OKU - Anggi Fatmayati, Aisah, Neng Karmila (JASEP, 2025)
Tempeh chips are a snack made from tempeh that can be used as a practical and ready-to-eat snack. This study aims to formulate a marketing strategy for tempeh chips. The study was conducted in Sri Mulya Village, Sinar Peninjauan District, OKU Regency. The research method used in this study is a case study method. The sampling method used a census method with a population of 5 tempeh chip entrepreneurs. The study shows that based on the results of the internal environmental analysis, strengths have a greater value than weaknesses. Meanwhile, based on external factors, opportunities have a greater value than threats. Therefore, the position of the tempeh chip business in Sri Mulya Village, Sinar Peninjauan District, OKU Regency is in Quadrant I, which means it is in a strategy to support an aggressive growth policy (growth-oriented strategy).